Kajian Kepuasan Mahasiswa Terhadap Pelayanan Universitas Kutai Kartanegara - Akbar, Ali (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
The main issue in improving the quality of higer education is increased competence, professionalism of educators and eduational staff to achieve the vision and mission of university through educational qualification standards, increased competence and professionalism. So universities are required to improve the quality of education that is able to produce excellent graduates in integrating the sciences with the value of ketagwaan, based on the implementation of education in harmony with incentives good Univercity Governance, integrated with personality coaching and academic network development, expected to improve the quality of managerial and university governance based on accountability, transparancy and efficiency with the framework of improving the quality of education that contribute to the development of national educattion and the realization of a hight competetive nation. The university of Kutai Kartanegara administration process related to the studens and the problems related to the administratative staff is study in this reseach. This reseach is intended to answer the problem ; first the level of student satisfaction to the university servics in terms of services expeywordienced with the expected service in accordance with the indicators of service quality. Secondly, a atrategy to increase student satisfaction with University of Kutai Kartanegara services. Keywords : Satisfaction, Service